Hypermanganesaemia with dystonia polycythemia and cirrhosis - Prem Chand; Zahra Ali Padhani; Rozmeen Akbar; Fazal Arain (Journal of the Pakistan Medical Association, 2022)
Hypermanganesaemia with dystonia, polycythemia, and cirrhosis (HMDPC) is a rare genetic and autosomal recessive disorder that occurs due to mutation of the SLC3A10 gene, which encodes the manganese (Mn) transporter in the body; as a result, Mn accumulates in the brain, liver and muscles. This accumulation leads to symptoms of generalized dystonia, polycythemia, and hypermanganesaemia. In this report, we present the case of a 2½-year-old baby girl (patient) with complaints of lower limb weakness and increased difficulty in walking for six months. Her laboratory test results showed deranged values with increased Mn levels in the body. The patient was put on six cycles of EDTA therapy, which showed an improvement in her condition. This case report is presented to create awareness about a rare genetic disorder with an effective treatment in some cases. Thus, more work and research is required to understand and develop better treatment options for this disease.